Telerehabilitation for chronic respiratory disease: a randomised controlled equivalence trial. Issue 7 (14th October 2021) - Cox, Narelle S; McDonald, Christine F; Mahal, Ajay; Alison, Jennifer A; Wootton, Richard; Hill, Catherine J; Zanaboni, Paolo; O'Halloran, Paul; Bondarenko, Janet; Macdonald, Heather; Barker, Kathryn; Crute, Hayley; et al.
Abstract : Rationale: Pulmonary rehabilitation is an effective treatment for people with chronic respiratory disease but is delivered to <5% of eligible individuals. This study investigated whether home-based telerehabilitation was equivalent to centre-based pulmonary rehabilitation in people with chronic respiratory disease. Methods: A multicentre randomised controlled trial with assessor blinding, powered for equivalence was undertaken. Individuals with a chronic respiratory disease referred to pulmonary rehabilitation at four participating sites (one rural) were eligible and randomised using concealed allocation to pulmonary rehabilitation or telerehabilitation. Both programmes were two times per week for 8 weeks. The primary outcome was change in Chronic Respiratory Disease Questionnaire Dyspnoea (CRQ-D) domain at end-rehabilitation, with a prespecified equivalence margin of 2.5 points. Follow-up was at 12 months. Secondary outcomes included exercise capacity, health-related quality of life, symptoms, self-efficacy and psychological well-being. Results: 142 participants were randomised to pulmonary rehabilitation or telerehabilitation with 96% and 97% included in the intention-to-treat analysis, respectively. There were no significant differences between groups for any outcome at either time point. Both groups achieved meaningful improvement in dyspnoea and exercise capacity at end-rehabilitation. However, we were unable to confirm equivalence of telerehabilitation for the primary outcome ΔCRQ-D at end-rehabilitation (mean difference (MD) (95% CI) −1 point (−3 to 1)), and inferiority of telerehabilitation could not be excluded at either time point (12-month follow-up: MD −1 point (95% CI −4 to 1)). At end-rehabilitation, telerehabilitation demonstrated equivalence for 6-minute walk distance (MD −6 m, 95% CI −26 to 15) with possibly superiority of telerehabilitation at 12 months (MD 14 m, 95% CI −10 to 38). Conclusion: telerehabilitation may not be equivalent to centre-based pulmonary rehabilitation for all outcomes, but is safe and achieves clinically meaningful benefits. When centre-based pulmonary rehabilitation is not available, telerehabilitation may provide an alternative programme model. Trial registration number: ACtelerehabilitationN12616000360415.